Speed dynamics in 60 m hurdles event - Larion, A.; Popa, C. (Journal of Sport and Kinetic Movement, 2019)
In this paper, we analized, using the video recordings, both the analytical analysis and the integral analysis of the 60 meters hurdles event. Subjects. The experiment was carried out on a group of 10 performance athletes of different sports clubs, at the Indoor National Championship. The athletes are between 18 and 25 years old and they are professional athletes for several years. They are also in the competition phase. Materials and methods. The study took place at the Indoor National Championship. The recordings of the reaction time, and the overall racing time were performed with the electronic timing system from the athletics hall. The running time between the hurdles and the time from the last hurdle to the finish line, were timed manually. The recording of the times were made in the two heats of seven, respectively eight competitors, as well as in the final. Results and discutions. After analyzing the intermediate times and the overall times of the heats and the final, the general chart records a continuous increase of the speed, reaching the maximum speed at the hurdle number 5. Conclusions. It has been demonstrated that the reaction time does not influence the overall time of the race nor its result. The data obtained becomes a basis for assessing the positive or negative state of athletes, the level at which an athlete should behave, at maximum speed and at the specific strength to be competitive at the highest level. Keywords: speed, hurdles, performance athletes.